Public awareness of dementia: A study in Botucatu, a medium-sized city in the State of São Paulo, Brazil - Schelp, Arthur Oscar [UNESP]; Nieri, Andrea Bruno [UNESP]; Hamamoto, Pedro Tadao [UNESP]; Bales, Alessandra Martins [UNESP]; Mendes-chiloff, Cristiane Lara [UNESP] (Associação de Neurologia Cognitiva e do Comportamento, 2008)
Dementia is a progressive and debilitating disease affecting an increasing number of people worldwide. Despite its importance, only a few studies have examined public awareness of dementia. We present a study of the public awareness of dementia in Botucatu, São Paulo, Brazil.

Demência é uma síndrome progressiva e inabilitante que afeta um número crescente de pessoas ao redor do mundo. A despeito de sua importância, poucos estudos tem examinado a conhecimento público sobre demência.
O conhecimento público da demência: um estudo em Botucatu, uma cidade de média dimensão no Estado de São Paulo, Brasil
Keywords: dementia; Alzheimer's disease; elderly population; public awareness.; demência; doença de Alzheimer; população idosa; percepção pública.